Emodin Alleviates Sodium Taurocholate-Induced Pancreatic Acinar Cell Injury via MicroRNA-30a-5p-Mediated Inhibition of High-Temperature Requirement A/Transforming Growth Factor Beta 1 Inflammatory Signaling - Xiang, Hong; Tao, Xufeng; Xia, Shilin; Qu, Jialin; Song, Huiyi; Liu, Jianjun; Shang, Dong (Frontiers in Immunology, 2017)
Pancreatitis is an inflammatory disease that is responsible for substantial morbidity and mortality, and it can induce pancreatic necrosis that starts within pancreatic acinar cells in severe cases. Emodin, a pleiotropic natural product isolated from the Chinese herb Rheum palmatum L., has effective anti-inflammatory activities. In this paper, we investigated the protective effects and molecular mechanism of emodin against sodium taurocholate (STC)-induced pancreatic acinar cells injury in vitro and in vivo; and the results showed that emodin could significantly alleviate STC-induced pancreatic acinar cells injury through decreasing trypsin, amylase and the release of inflammatory factors (TNF-α, IL-1β and IL-6). Also, we found that emodin could significantly down-regulate the HTRA1, IL-33, MyD88, TRAF-6 and NF-κB protein levels, but up-regulate the TGF-β1 protein level. These results indicated that emodin alleviated pancreatic acinar cells injury mainly through inhibiting HTRA1/TGF-β1 signalling pathway, and this finding was further proved by the HTRA1 overexpression experiments. In addition, the inflammatory regulator miRNA-30a-5p (miR-30a-5p) was confirmed to be a transcriptional brake that controls the HTRA1 gene through using a dual luciferase reporter assay, and it was up-regulated by emodin in pancreatic acinar cells. Furthermore, the pancreatic protective effects and anti-inflammatory activities of emodin were all abrogated with both miR-30a-5p inhibitor in vitro and miR-30a-5p antagomir in vivo. Collectively, these results demonstrate that miR-30a-5p/HTRA1 are the target of emodin-mediated attenuation of pancreatic acinar cell injury in pancreatitis, thus providing the foundation for further development of this natural product for medical therapy.